The Position of Women Witnesses in Islamic Law: An Analysis of Women's Contribution to the Judicial Process in Indonesia - Fadilla Syahriani; Navisa Latifa Auliya (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study comprehensively examines the position of female witnesses in Islamic law, focusing on the scholarly debates regarding the acceptance or rejection of female testimony, particularly in cases related to criminal law (hudud). Using a qualitative approach, this study analyzes the theoretical and legal foundations that underpin the role of female witnesses and evaluates their application in Indonesia's modern judicial system. The main sources of this research include classical texts of Islamic law, the views of scholars, and applicable positive legal regulations. This research is conducted as a library study, drawing from classical texts of Islamic law, scholarly views, and relevant positive legal regulations. The findings reveal differing interpretations regarding women's testimony, with some classical scholars placing less weight on it compared to men, while contemporary perspectives tend to be more inclusive, aligning with principles of justice and equality.The results show that, although challenges remain in implementation, the role of female witnesses is increasingly recognised and accepted in the Indonesian judiciary, especially in cases that require a female perspective. The main contribution of this research is to provide insights that strengthen the discussion on gender justice in Islamic law, while offering recommendations to optimise women's participation in the legal process. These recommendations include strengthening policies that ensure witness equality based on the principles of maqasid al-shariah (the objectives of sharia) and applying norms that are more contextualised to social realities in Indonesia. As such, this research contributes to the development of a more just and inclusive justice system, capable of addressing contemporary legal and social challenges.